Morphometric and Meristic Characters of Putak Fish (Notopterus notopterus) in the Rokan River Basin Rokan Hilir Regency Riau - Munte, Aini; Setyoko, Setyoko; Jayanthi, Sri (Jurnal Perikanan Universitas Gadjah Mada, 2024)
Putak fish (Notopterus notopterus) is a type of fish native to Indonesia which is protected based on Government Regulation Number 7 of 1999. Habitat and environmental factors are one of the factors that influence the survival, morphological and biological characteristics of putak fish. The waters of Rokan Hilir Regency, Riau, are one of the habitats of the putak fish (Notopterus notopterus). This research aims to determine the morphological, biological and physicochemical characteristics of the aquatic environment of putak fish (Notopterus notopterus) in the Rokan River, Rokan Hilir Regency, Riau. The method used in this research is a two-station observation method, identifying research stations using a purposive sampling method. Station 1 is in a community settlement and Station 2 is in an oil palm plantation on the riverbank. Data analysis uses quantitative description with simple linear regression. The results showed that at each station there were 22 fish consisting of 11 male fish and 11 female fish. The results of the morphological characteristics of total length are more dominant in female fish with an average length at station 1 of 211.91 mm and an average of 255.91 mm at station 2 compared to male fish with an average length of 211.91 mm exceeding 178.55 mm at station 1. and an average of 222.00 mm at station 2. Regression analysis shows that the morphology of putak fish (Notopterus notopterus) is in a positive biometric criteria state or at station 2 with TL/SL characters, while the other characters are negative. biomass state. The results of data on the biological characteristics of putak fish (Notopterus notopterus) at station 2 are higher than at station 1. The physicochemical factors of the two stations are differences in temperature, where the temperature at station 2 is higher than at station 1.